Isokinetic hamstring and quadriceps strength interpretation guideline for football (soccer) players with ACL reconstruction: a Delphi consensus study in the Netherlands - van der Horst, N.; van Denderen, R. (Science and Medicine in Football, 2022)
Strength testing is a key part of rehabilitation and return to sport (RTS) decision making for football players after anterior cruciate ligament reconstruction (ACLR). Isokinetic testing has been the gold standard for strength measurement for decades, but a uniform protocol and clinical implications of test results are lacking. Therefore, this study aimed to 1) develop a uniform protocol for football players based on knowledge and experience from experts in the field of ACL rehabilitation and 2) clarify the clinical interpretation of different isokinetic test outcomes. In a structured Delphi consensus procedure 42 experts (98% full response rate) fulfilled three rounds that involved a survey, content analysis and anonymised feedback report for each round. Surveys addressed the isokinetic protocol, evaluation report and torque-angle curve of the isokinetic test for strength evaluation in football players after ACLR. The final protocol consisted of concentric knee flexion and extension isokinetic testing with 5 repetitions at 60°/sec, 20 repetitions at 180°/sec and 15 repetitions at 300°/sec and 60seconds rest between sets. All parameters were deemed valuable, with Peak Torque, Max Rep Total Work, Total Work, Range of Motion and Agonist to Antagonist ratio being considered key for clinical interpretation. For qualitative assessment, it was advised to assess the shape, course, volume, potential dips, peak, and build-up to the peak of the parabola. This Delphi consensus study provided a guideline for data collection and clinical interpretation of isokinetic strength testing in football players after ACLR.